Molecular detection of Listeria monocytogenes in refrigerated raw milk and geospatial distribution in Brazilian small farms - STEINLE, Jackieline Sampaio; BERTOLINI, Amanda Bezerra; PEREIRA, Juliano Gonçalves; PAES, Antonio Carlos; SILVA, Laís Pereira da; LEITE, Bruna dos Santos; RIBEIRO, Talytta Motta; AIRES, Isabella Neves; RANGEL, Marcos Vinícius; CURCI, Vera Cláudia Magalhães; FAGNANI, Rafael; BERTOZZO, Thainá Valente; et al. (Food Science and Technology, 2025)
Listeriosis is a zoonosis whose etiological agent is the bacterium Listeria monocytogenes. Milk and dairy products are considered excellent substrates for the development of L. monocytogenes. Using conventional PCR, L. monocytogenes was investigated in 102 samples of raw milk from bulk tanks of small farms. Also, microbiological analysis was performed in positive samples by PCR. The primers such as PRS, LM1/LM2, inlA, inlC, and inlJ were used for spatial analysis. PRS indicated a positivity of 20.58%, and inlJ and inlC primers indicated 21.57%. The primers inlA and LM1/LM2 were negative. Our findings indicate it was possible to achieve effective molecular detection of L monocytogenes in the tank milk samples evaluated, in detriment to microbiological culture, in which there was no isolation.